2014
DOI: 10.1063/1.4899315
|View full text |Cite
|
Sign up to set email alerts
|

An in situ tensile test apparatus for polymers in high pressure hydrogen

Abstract: Degradation of material properties by high-pressure hydrogen is an important factor in determining the safety and reliability of materials used in high-pressure hydrogen storage and delivery. Hydrogen damage mechanisms have a time dependence that is linked to hydrogen outgassing after exposure to the hydrogen atmosphere that makes ex situ measurements of mechanical properties problematic. Designing in situ measurement instruments for high-pressure hydrogen is challenging due to known hydrogen incompatibility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…25,26 To clarify, material degradation of this sort may occur any time the pressure drop is rapid compared to diffusion of hydrogen within the material under study. In previous work by Alvine et al, 36 it has been observed that material properties, such as tensile strength, that change with hydrogen exposure will recover gradually with time as hydrogen diffuses out of the material. 36 For HDPE of cross section 12.7 mm × 12.7 mm (½ in.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…25,26 To clarify, material degradation of this sort may occur any time the pressure drop is rapid compared to diffusion of hydrogen within the material under study. In previous work by Alvine et al, 36 it has been observed that material properties, such as tensile strength, that change with hydrogen exposure will recover gradually with time as hydrogen diffuses out of the material. 36 For HDPE of cross section 12.7 mm × 12.7 mm (½ in.…”
Section: Introductionmentioning
confidence: 92%
“…In previous work by Alvine et al, 36 it has been observed that material properties, such as tensile strength, that change with hydrogen exposure will recover gradually with time as hydrogen diffuses out of the material. 36 For HDPE of cross section 12.7 mm × 12.7 mm (½ in. × ½ in.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…While there is an abundance of information on the hydrogen degradation mechanisms in metals and some ceramics, there is still little information in the literature about the detrimental effects of hydrogen on polymers (Castagnet et al 2010, Jaravel et al 2011, Boyer et al 2014, Alvine et al 2014. Absorption in polymers differs from that of absorption in metals (Fukai 2005) in that disassociation of the hydrogen is not expected to occur within the material.…”
Section: Impact Of Hydrogen and Cryogenic Temperatures On Polymer Promentioning
confidence: 99%